Inactivation of listeria monocytogenes by pulsed uv illumination and photorepair recovery of uv-damaged cells - Mohd Nizam Lani (University of Strathclyde, 2011)
The work presented in this thesis is concerned with an investigation of the effects of ultraviolet radiation on the inactivation and on the subsequent photorepair(photoreactivation) of UV-damage by exposure to longer wavelength light of Listeria monocytogenes NCTC 11994 (serotype 4b).